PENINGKATAN AKTIVITAS BELAJAR BAHASA INDONESIA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DI KELAS VIII – 2 SMP NEGERI 4 MEDAN - SARIFAH HANUM (JURNAL HANDAYANI PGSD FIP UNIMED, 2014)
The research applicated the cooperative learning model type Cooperative Integrated Reading and Composition (CIRC) as the way for increasing the studying activity which will be impact the student studying result on subjects of Indonesian Language. The application of model is held in class acting research during two cycles with two times meeting (Teaching – Learning Activity) every cycles. In order that the data in this research is student studying activity and student studying result after applicated the cooperative learning model type Cooperative Integrated Reading and Composition (CIRC) by research subjects is all of students in class of VIII – 2 which amounts of 34 students. The activity data is gotten from student observation every cycles, the studying result data is gotten from test every cycles. The research result is showed; 1) By using the cooperative learning model type Cooperative Integrated Reading and Composition (CIRC), the student activity data accord the observer observation on cycle II among other writing / reading (41%), doing (28%), asking for friends (14%), asking for the teacher (11%), and not relevant with teaching – learning process (7%) and student activity accord the observation on cycle II among others writing / reading (17%), doing (51%), asking for the friends (14%), asking for the teacher (11%) and not relevant with teaching – learning process (1%). 2) The student studying result drom cycle I to cycle II occur the increasing. The student studying result by applicated cooperative learning model type Cooperative Integrated Reading and Composition (CIRC) on formative I and formative II is shown 20 student pass indivually and class which the 51,06% and 30 students pass individally by 88,23% pass class, by average in cycle I to cycle II is 65,29 and 86,47. It means cycle I and cycle II occur the classical increasing result according with Indonesian Language CCM is 70. Keywords: cooperative learning model type Cooperative Integrated Reading and Composition (CIRC), Students; s activity, the student studying result